Knowledge and information sources on standard precautions and infection control of health sciences students at King Saud bin Abdulaziz University for Health Sciences, Saudi Arabia, Riyadh - Abdullah Khubrani; Meshal Albesher; Abdulah Alkahtani; Faisal Alamri; Majid Alshamrani; Emad Masuadi (Elsevier, 2018)
Background: Only one study has been conducted in Saudi Arabia to assess medical students' knowledge of standard precautions (SPs) and infection control (IC). In this study, we examined knowledge of SPs and IC among clinical students attending the King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia. Methods: In this cross-sectional study, we targeted clinical students from the following five colleges: Medicine (fifth and sixth years); Dentistry (second semester of the third, fourth, fifth, and sixth years); Applied Medical Sciences (third and fourth years); Nursing (third and fourth years); and Pharmacy (third, fourth, and fifth years). The data collection instrument was an adopted 41-item questionnaire that measured knowledge of SPs and IC in five domains. A score of ≥24 (60%) indicated sufficient knowledge. Results: The participants comprised 129 students (67 men). The proportions of participants from each college were: Medicine, 58.1% (n = 75); Dentistry, 14% (n = 18); Applied Medical Sciences, 13.2% (n = 17); Nursing, 10.9% (n = 14); and Pharmacy, 3.9% (n = 5). Most students (73.6%) demonstrated sufficient knowledge (men, 67.2% and women, 80.6%). The highest scores were obtained for the domains "general concept of SPs", "hand hygiene", and "personal protective equipment", whereas the lowest scores were obtained for "disposal of and injuries from sharp objects" and "health-care providers' care". The main information source was formal curricular teaching. Conclusions: In Saudi Arabia, students' knowledge of SPs and IC is satisfactory, with no significant differences between the sexes or between colleges. Thus, formal curricular teaching is an effective way to increase students' knowledge of SPs and IC. Keywords: Education, Hygiene, Infection control, Standard precautions, Medical students, Saudi Arabia